2017
DOI: 10.1007/s10637-017-0503-7
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine and antihelmintic mebendazole potentiate temozolomide in resistant gliomas

Abstract: Glioblastoma (GBM) is a very aggressive tumor that has not had substantial therapeutic improvement since the introduction of temozolomide (TMZ) in combination with radiotherapy. Combining TMZ with other chemotherapeutic agents is a strategy that could be further explored for GBM. To search for molecular predictors of TMZ resistance, the TCGA (The Cancer Genome Atlas) database was utilized to assess the impact of specific genes on TMZ response. Patients whose tumors expressed low levels of FGFR3 and AKT2 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…Reduced DNA synthesis, morphology, SA-β-gal, growth arrest, p21 Cip1 [55] Irinotecan SGC-7901, MKN-45 SA-β-gal [56] A549, HCT116 Reduced DNA synthesis, morphology, SA-β-gal, growth arrest, p21 Cip1 [55] Alkylating agents Busulfan Rat-derived BMSCs and ADSCs SA-β-gal [42] WI38 Growth arrest, SA-β-gal [57] U2OS, MG63 SA-β-gal [58] WI38 SA-β-gal [59] Murine hematopoietic cells SA-β-gal, p16 INK4 , p19 INK4 [60] Temozolomide Patient derived glioma cells Cell cycle arrest, polyploidy, morphology [61] GL261 SAHF (H3K9Me3), p53, Rb [62] LN229 SA-β-gal, cell cycle arrest, SASP (IL-6, IL-8) [63] In vivo (p16-3MR) mouse model p16 INK4 [28] Carmustine GL261 SAHF (H3K9Me3), p53, Rb [62] Dacarbazine A375, B16F10 SASP [64] Cyclophosphamide HSC-bcl2 lymphoma SA-β-gal, p53, p16 INK4 [65] Melphalan Multiple myeloma mouse model SA-β-gal [66] Mitomycin C A549 Growth arrest, SA-β-gal, yH2AX, morphology [67]…”
Section: Drug Class Drug Name Model/cell Line Senescence Marker Refermentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced DNA synthesis, morphology, SA-β-gal, growth arrest, p21 Cip1 [55] Irinotecan SGC-7901, MKN-45 SA-β-gal [56] A549, HCT116 Reduced DNA synthesis, morphology, SA-β-gal, growth arrest, p21 Cip1 [55] Alkylating agents Busulfan Rat-derived BMSCs and ADSCs SA-β-gal [42] WI38 Growth arrest, SA-β-gal [57] U2OS, MG63 SA-β-gal [58] WI38 SA-β-gal [59] Murine hematopoietic cells SA-β-gal, p16 INK4 , p19 INK4 [60] Temozolomide Patient derived glioma cells Cell cycle arrest, polyploidy, morphology [61] GL261 SAHF (H3K9Me3), p53, Rb [62] LN229 SA-β-gal, cell cycle arrest, SASP (IL-6, IL-8) [63] In vivo (p16-3MR) mouse model p16 INK4 [28] Carmustine GL261 SAHF (H3K9Me3), p53, Rb [62] Dacarbazine A375, B16F10 SASP [64] Cyclophosphamide HSC-bcl2 lymphoma SA-β-gal, p53, p16 INK4 [65] Melphalan Multiple myeloma mouse model SA-β-gal [66] Mitomycin C A549 Growth arrest, SA-β-gal, yH2AX, morphology [67]…”
Section: Drug Class Drug Name Model/cell Line Senescence Marker Refermentioning
confidence: 99%
“…Temozolomide is an oral alkylating agent that has been a cornerstone in the treatment of brain tumors such as astrocytomas and glioblastoma multiforme. Temozolomide is capable of inducing features of senescence in several immortalized human, murine and patient-derived glioma cell lines [61,62]. Temozolomide induces senescence by introducing the O 6 MeG lesion, which results in the activation of the DNA Damage Repair Response (DDR) ATR-CHK1 pathway, eventually forcing a p21 Cip1 -mediated growth arrest [63].…”
Section: Alkylating Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, MBZ has been recognized as an attractive candidate for drug repurposing in various models of human cancers [7][8][9][10][11][12]. Its anti-cancer properties were notably demonstrated in gliomas [11,14,27] and there is currently 3 ongoing clinical trials in high-grade gliomas in both adult and pediatric patients (NCT01729260, NCT02644291 and NCT01837862). Furthermore, a recent phase I trial demonstrated that administration of MBZ concomitantly with radiotherapy and temozolomide chemotherapy was safe in high-grade glioma patients [28] Although multiple studies have highlighted different mechanisms of action of MBZ in cancer cells [12][13][14][15][16], including its effects on the microtubule network [8,11,14,17,18], its precise molecular target(s) in tumor cells remained to be ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…VBL binds to tubulin and inhibits the formation of microtubules, causing disruption of the assembly of mitotic spindles and the arrest of tumor cells in the M phase of the cell cycle [ 1 ]. VBL, which is marketed under the Velban brand name, among others, is a chemotherapy drug that is usually used in combination with other drugs to treat different types of cancer, including breast cancer, Hodgkin’s lymphoma, brain cancer, prostate cancer, and testicular cancer [ 2 , 3 , 4 , 5 ]. However, its cytotoxicity and nonspecific biodistribution are the major challenges of VBL therapy, as they cause severe side effects in patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%